Design of bright, fiber-coupled and fully factorable photon pair sources for quantum information processing - Vicent, L; U'Ren, AB; Zhang, L; Walmsley, I (2008)
We derive conditions for full spatio-temporal factorability in non-collinear type-I spontaneous parametric downconversion. We show that fulfilment of these conditions leads to a higher single-mode fiber-coupled brightness, compared to sources rendered factorable through spectral filtering. © 2008 Optical Society of America.